Evaluasi Pengelolaan Limbah cair dan Limbah Padat Bahan Berbahaya dan Beracundi Industri Cat PT.X - Verina Elvira; Mila Dirgawati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The manufacturing sector is widespread, and like with any other sector, it generates trash in the course of its operations. According to Government Regulation Number22, all service providers are obligated to engage in management. Finding out what kind of waste management system PT.Xuses is the main goal of this study. The data is gathered from primary and secondary sources. Based on the findings, liquid waste management has achieved a highly effective 99% removal of BOD5 and TSS, while solid waste management has achieved a suitable value of 70.46 percent.The recommendation given is that for liquid waste, test more parameters, not just 3 parameters, and for solid waste, make improvements based on parameters that are not by the applicable references, such as replacing the wastewater treatment plant with a Jumbo Bag, and so on